Fecal Microbial Transplant After Ileocolic Resection Reduces Ileitis but Restores Colitis in IL-10−/− Mice. Issue 7 (July 2015) - Perry, Troy; Jovel, Juan; Patterson, Jordan; Wong, Gane; Fedorak, Richard N.; Thiesen, Aducio; Dicken, Bryan; Madsen, Karen L.
Abstract : Background: Ileocolic resection (ICR) is frequently performed for Crohn's disease; however, disease commonly recurs early in the neoterminal ileum. The aim of this study was to use the IL-10 −/− mouse to determine the effects of ICR on gut microbiome and immune function and if postoperative fecal microbial transplant (FMT) would improve disease. Methods: ICR was performed in 129S1/SvlmJ IL10 −/− mice followed by FMT using stool from wild-type mice. Sham-transplant mice received their own stool. Stool samples were collected on day 0, day 13 (after ICR), and day 27 (after FMT) for whole metagenome shot-gun sequencing. Mucosal-associated bacteria were quantified with quantitative PCR and visualized by fluorescent in situ hybridization. Tissue cytokines were measured with multiplex arrays and mononuclear phagocyte populations by flow cytometry. Results: Surgery induced microbial functional and taxonomic shifts, decreased diversity, and depleted Bacteroidia and Clostridia. ICR mice had reduced colitis but worse ileitis with bacterial overgrowth, increased translocation, and reduction in tissue macrophages. FMT prevented ileitis but restored colitis and allowed for a bloom of γ-proteobacteria. In the colon, ICR and sham transplant were associated with recruitment of tolerogenic dendritic cells, whereas FMT shifted these immune cell subsets to control profiles along with increasing cytokine levels. Conclusions: This study suggests that surgical-induced immune dysfunction and microbial dysbiosis with impaired clearance may be the underlying cause of the early ulcerations found in the ileum of patients with Crohn's disease after ICR. FMT has an immunostimulatory effect on the postoperative intestine, which was beneficial in preventing ileitis, but detrimental in restoring colonic injury after surgery. Abstract : Article first published online 19 May 2015.Supplemental Digital Content is Available in the Text.